A review for Ralitsa Kostadinovaâ€™s book â€œSuspended sentence under Bulgarian Criminal Lawâ€ - Ilkova, Ralitsa (Law Journal of New Bulgarian University, 2021)
The review is dedicated to the monograph entitled â€œSuspended Sentence under Bulgarian Criminal Lawâ€ by Ralitsa Kostadinova. In the book the author has pointed her scientific research in an academic area, namely that of suspended sentence, which so far has not been subject of a thorough and in-depth scientific analysis in Bulgaria, but at the same time it is of great practical significance in particular with regard to the work of the judicial bodies. The monograph under review undoubtedly contributes to the criminal legal theory.